The empusium : a health resort horror story [large type] - Tokarczuk, Olga, 1962- (Random House Large Print, 2024)
"September 1913. A young Pole suffering from tuberculosis arrives at Wilhelm Opitz's Guesthouse for Gentlemen in the village of Görbersdorf, a health resort in the Silesian mountains. Every evening the residents gather to imbibe the hallucinogenic local liqueur and debate the great issues of the day: Monarchy or democracy? Do devils exist? Are women born inferior? War or peace? Meanwhile, disturbing things are happening in the guesthouse and the surrounding hills. Someone--or something--seems to be watching, attempting to infiltrate this cloistered world. Little does the newcomer realize, as he tries to unravel both the truths within himself and the mystery of the sinister forces beyond, that they have already chosen their next target."--Back cover.